2017
DOI: 10.1186/s40645-017-0129-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of slight thinning of managed coniferous forest on landscape appreciation and psychological restoration

Abstract: We investigated the influence of slight thinning (percentage of woods: 16.6%, basal area: 9.3%) on landscape appreciation and the psychological restorative effect of an on-site setting by exposing respondents to an ordinarily managed coniferous woodland. The experiments were conducted in an experimental plot in the same coniferous woodland in May (unthinned) and October 2013 (thinned). The respondents were the same 15 individuals for both experiments. Respondents were individually exposed to the enclosed plot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
39
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 46 publications
10
39
2
1
Order By: Relevance
“…Their results show that subjects in forest environments had a lower level of negative emotions (e.g., tension-anxiety, confusion, fatigue, depression) and a higher level of vigor than those in urban environments, demonstrating the psychological benefits of forests in mental health. Similar results were reported by Takayama et al, who found that subjects' tension-anxiety, depression-dejection, and confusion decreased after viewing forests [8]. Other than POMS, some studies have assessed the change in anxiety by using the State-Trait Anxiety Inventory (STAI) [9,10].…”
Section: Introductionsupporting
confidence: 77%
“…Their results show that subjects in forest environments had a lower level of negative emotions (e.g., tension-anxiety, confusion, fatigue, depression) and a higher level of vigor than those in urban environments, demonstrating the psychological benefits of forests in mental health. Similar results were reported by Takayama et al, who found that subjects' tension-anxiety, depression-dejection, and confusion decreased after viewing forests [8]. Other than POMS, some studies have assessed the change in anxiety by using the State-Trait Anxiety Inventory (STAI) [9,10].…”
Section: Introductionsupporting
confidence: 77%
“…It is therefore possible that the time period during which respondents were exposed to the stimulus was not exactly 15 min in length. It is worth mentioning, however, that the walks to the two analyzed environments were conducted through either the urban street environment or the forest (Figure 1), so only one environment was able to influence each group [46].…”
Section: Limitationsmentioning
confidence: 99%
“…To balance the need to quickly perform the tests and the need to obtain reliable results, an optimal sample size was used. Previous research indicates that a sample size of 12-16 participants is sufficient to draw significant conclusions in forest therapy experiments [18,28], and thus the groups of 23 patients with psychotic disorders and 27 patients with affective disorders included in this study are large enough to provide valuable information.…”
Section: Participantsmentioning
confidence: 99%
“…If this is so, this activity could be helpful as an additional therapy in treating some mental health problems, such as anxiety and depression. Alternatively, staying in an environment not appropriate for forest therapy, such as a forest without a view and with a dense understory, could induce fear [28], which is not a desired effect. For this reason, it is unclear whether or not forest recreation will induce a therapeutic effect in mental hospital patients.…”
Section: Introductionmentioning
confidence: 99%